The naturalization of love ideology in ‘Tabola Bale’ Lyrics: A Roland Barthes semiotic analysis - Sasikirana, Aulia Nabila; Basit, Abdul (Universitas Muhammadiyah Malang, 2026)
Popular song lyrics often function as cultural texts that express emotional experiences while simultaneously reflecting broader social meanings. One example is “Tabola Bale,” a widely circulated song that combines Indonesian and Eastern Indonesian linguistic expressions in narrating romantic relationships. This study examines how the lyrics construct meanings of cultural communication through a semiotic analysis. The research employs a qualitative interpretive approach with a single-case design by treating the song lyrics as a cultural text analyzed using Roland Barthes’ three levels of signification: denotation, connotation, and myth. The findings show that at the denotative level the lyrics represent emotional experiences such as attraction, emotional unease, and expectations within romantic relationships. At the connotative level, expressions such as tabola bale, hati susah, and mete associate love with persistent emotional intensity and deep affective attachment. At the mythic level, these recurring signs construct an ideological narrative in which emotional restlessness is framed as evidence of sincere love, while marriage is positioned as the ideal orientation of romantic relationships. As a single-case interpretive study, the findings demonstrate how a popular song lyric can construct cultural meanings of love, gender relations, and relational commitment through symbolic representation. Lirik lagu populer sering dipahami sebagai teks budaya yang mengekspresikan pengalaman emosional sekaligus merefleksikan makna sosial yang lebih luas. Salah satu contohnya adalah lagu “Tabola Bale”, sebuah lagu yang beredar luas dan menggunakan perpaduan bahasa Indonesia serta ungkapan bahasa Indonesia Timur dalam narasi relasi romantis. Penelitian ini mengkaji bagaimana lirik lagu tersebut membangun makna komunikasi budaya melalui analisis semiotika. Penelitian menggunakan pendekatan kualitatif interpretatif dengan desain studi kasus tunggal, dengan memperlakukan lirik lagu sebagai teks budaya yang dianalisis menggunakan tiga tingkat pemaknaan Roland Barthes, yaitu denotatif, konotatif, dan mitos.Hasil penelitian menunjukkan bahwa pada tingkat denotatif lirik merepresentasikan pengalaman emosional seperti ketertarikan, kegelisahan perasaan, dan harapan dalam relasi romantis. Pada tingkat konotatif, ungkapan seperti tabola bale, hati susah, dan mete membangun asosiasi antara cinta dan intensitas emosional yang terus tertuju pada pasangan. Pada tingkat mitos, tanda-tanda yang berulang tersebut membentuk narasi ideologis yang menempatkan kegelisahan emosional sebagai bukti ketulusan cinta serta memosisikan pernikahan sebagai orientasi ideal dalam hubungan romantis. Sebagai studi interpretatif dengan objek satu lagu, penelitian ini menunjukkan bagaimana lirik lagu populer dapat membangun makna budaya mengenai cinta, relasi gender, dan komitmen melalui representasi simbolik.